The platform will undergo maintenance on Sep 14 at about 9:30 AM EST and will be unavailable for approximately 1 hour.
2017
DOI: 10.5380/rf.v47i1.44018
|View full text |Cite
|
Sign up to set email alerts
|

USO DA MICROBIOLIZAÇÃO CONTRA Lasiodiplodia theobromae EM SEMENTES DE PINUS SPP.

Abstract: ResumoO uso de agentes biocontroladores em doenças de plantas é uma alterativa aos produtos químicos que vem conquistando seu espaço, isso, devido à condição atual de proteção e manutenção do meio ambiente.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 9 publications
0
2
0
Order By: Relevance
“…Evaluating the antagonistic action of six biological products, including Trichodermil ® and Trichodel ® , Maciel et al (2017) found that antagonistic agents acted by expanding the seedlings final quality variables in Pinus taeda L. and Pinus elliottii Engel., not significantly interfering with seedling emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Evaluating the antagonistic action of six biological products, including Trichodermil ® and Trichodel ® , Maciel et al (2017) found that antagonistic agents acted by expanding the seedlings final quality variables in Pinus taeda L. and Pinus elliottii Engel., not significantly interfering with seedling emergence.…”
Section: Discussionmentioning
confidence: 99%
“…Oliveira et al (2016) studied B. subtilis inoculation in common bean seed lots with low and high vigor and observed an increase in seedling dry weight. Maciel et al (2017) reported growth in Pinus spp. seedlings from seeds microbiolized with B. subtilis.…”
Section: Produção De Feijão Vagem Oriunda De Sementes Tratadas Com Ba...mentioning
confidence: 99%
“…Belonging to the genre Lasiodiplodia, family Botryosphariaceae, order Botryosphaeriales, class Dothideomycetes and phylum Ascomycota the fungus Lasiodiplodia pseudotheobromae arise of a split of the specie Lasiodiplodia theobromae (Adetunji and Oleke, 2013). The fungus L. pseudotheobromae is an opportunist pathogen, cause rottenness in seeds, decrease germinative potential of the plants and there are several host plants for it (Maciel et al, 2017;Machado and Pinho, 2013). The fungus L. pseudotheobromae has excellent herbicidal activity against weed (Adetunji et al, 2017;Adetunji et al, 2018).…”
Section: Introductionmentioning
confidence: 99%